Cross-cultural validation of the FACE-Q Satisfaction with Facial Appearance Overall Scale (FACE-Q SFAOS) in Brazilian rhytidoplasty patients (Clinics, 2020)
OBJECTIVES: This study aimed to culturally validate the FACE-Q - Satisfaction with Facial Appearance Overall Scale (Face-Q SFAOS) in a population of Brazilian rhytidoplasty patients. METHOD: Authorization for the translation and validation of the questionnaire was obtained from the FACE-Q SFAOS distribution rights holders. The FACE-Q SFAOS was translated and then back-translated. For cultural validation, a total of 57 women were selected 5 to 8 months after undergoing rhytidoplasty. Twenty of them participated in the cultural adaptation, 30 participated in the reproducibility analysis, and 57 participated in the construct validation. RESULTS: The analysis identified two factors (general appearance and face geometry) that exhibited excellent internal consistency. The total satisfaction score, which comprised nine items, also presented excellent internal consistency. Good reproducibility was found for Overall Appearance, Geometry and Total. There was a difference in the satisfaction means (total and factors) between procedure locations; patients undergoing frontal, upper eyelid and lower eyelid procedures were less satisfied than those who did not undergo such procedures. Satisfaction was higher with geometry than with overall face appearance. CONCLUSION: The FACE-Q SFAOS was adapted to the cultural context of Brazilian rhytidoplasty patients and was reproducible, and the scale exhibited face, content and construct validity.